solve the above equation and verify the solution
Attachments:
![](https://hi-static.z-dn.net/files/d85/b2c8847aff7645b15a7ceefc5b7866f6.jpg)
Answers
Answered by
1
If it helps please mark me in Brainleist...
(◕‿◕)
Attachments:
![](https://hi-static.z-dn.net/files/dbf/cf0bf86cd2669f3c124f8c263b688893.jpg)
PriteshBang:
as ur wish...
Answered by
1
Answer: -5/4
Step-by-step explanation:
(3x+4)(2x+3)=(x+1)(6x+7)
6x^2+9x+8x+12=6x^2+7x+6x+7
6x^2+17x+12=6x^2+13x+7
6x^2-6x^2+17x+12=13x+7
17x+12=13x+7
17x-13x=7-12
4x= -5
x= -5/4
Similar questions